Analysis of the right of reconciliation for wives from the perspective of gender justice and Islamic law in Indonesia - Ahdiyatul Hidayah (An-Nisa’ Journal of Gender Studies, 2025)
In reconciliation practices, wives’ consent is often neglected and interpreted differently across Islamic schools, while gender justice emphasizes equality in marriage. The husband’s unilateral right to reclaim his wife after talaq raj‘i reflects persistent male dominance within marital relations. This study analyzes wives’ reconciliation rights from gender justice and Islamic law in Indonesia, identifying transformation of Islamic family law, Compilation of Islamic Law (KHI) reconstruction, shift from male authority to participatory relational justice. This study employed a qualitative normative-juridical approach using library research. Primary and secondary data sources were analyzed through content analysis and comparative analysis between classical fiqh perspectives, the KHI, and gender justice perspectives. This study finds: (1) Islamic family law transforms toward gender justice via women’s rights, husbands’ ethical duties, khulu’, and equal marital relations; (2) KHI reconstructs reconciliation by requiring wife’s consent, reinforcing her dignity, autonomy, and gender justice; (3) comparing classical law with gender perspectives shows a shift from absolute male authority to participatory reconciliation and relational justice. This study found a transformation of Islamic family law toward gender justice, the reconstruction of the KHI through the requirement of the wife’s consent, and a shift from absolute male authority toward participatory and relational reconciliation. This study contributes to integrating gender justice and maqāṣid al-syarī‘ah within Islamic law, while also encouraging the strengthening of KHI implementation, judicial training, and the inclusion of wife consent clauses in marriage contracts.